Monitoring physical performance and training load in young surf athletes - Silva, B.; Cruz, G.; Rocha-Rodrigues, S.; Clemente, F. M. (Journal of Human Sport & Exercise, 2021)
We aimed to study physical performance and monitor training load (both internal and external) during 12 weeks (3 times per week) and analyse the hypothetical association between physical performance and training load of competitive junior surfers. Twelve competitive surfers voluntarily participated (aged 16.00 ± 1.00y) and completed anthropometric and 8 physical performance tests including weight-bearing dorsiflexion test, functional movement screen, star excursion balance test, squat jump and countermovement jump, sprint & endurance paddling, and breath-hold capacity. Moreover, athletes were monitored by using a heart rate (HR) sensor and global position system (GPS) during each training session (n = 36). For internal load (IL), HR, rating of perceived exertion RPE, duration*RPE were used as variables and for external load (EL), duration, total distance, average and maximum speed and pace were considered for analysis. No significant correlations were found between physical performance tests and the training load variables. Significant correlations were found between IL (time*RPE), total distance (r = .58, p < .01), maximum speed (r = .43, p = .04) and duration (r = .60, p < .01). The HR was positively associated with average speed (r = .45, p = .04), pace (r = .43, p = .04), maximum speed (r = .64, p < .01). Total distance, average HR and average speed significantly predicted IL during training F(4.18) = 3.17; p = .04; R2 = .48. Data suggests that subjective instruments like RPE seems to be a good instrument to assess the training load in surf training. In terms of training for surfing, maximum speed seems to be a determinant factor in the estimation of IL perception.